A socio-economic environment that transformed farmers' households into merchants. Issue 1 (1st December 2022) - Tajidan, Tajidan; Halil, Halil; Efendy, Efendy; Fernandez, Fransiskus Xaverius Edy; Nabilah, Sharfina; Muttaqin, M. Zaenul; Sukmana, Febrian Humaidi
Abstract: This study aims to reveal the socio-economic background of the household that led the farmer's household to transform into a farmer at the same time as a healthy vegetable trader, as well as to design the marketing mix strategy plus motivation and management (4'P + 2'M). Data collection uses a triangular method, which is a combination of structured interview, in-depth interviews, and observation techniques at farms and places where healthy vegetables are sold. Data analysis used mixed models, namely quantitative and qualitative. Quantitative analysis applies descriptive statistics, while qualitative methods apply comparative analysis and desk studies. The results of the study show that the income obtained from agricultural products is not sufficient for economic needs as a trigger for them to double work as farmers and traders, as well as optimizing the use of household resources through the application of marketing mix strategies plus motivation and management, so that they are able to increase their household income.